Correlation of self-management and social support with quality of life in patients with chronic kidney disease undergoing hemodialysis: A cross-sectional study from Kerala, India - Shewta Ramesh; Chitra Tomy; Rajesh R Nair; Jeby Jose Olickal; Joseph K Joseph; Kavumpurath Raman Thankappan (Elsevier, 2024)
Introduction: Chronic Kidney Disease (CKD) is a progressive condition that impacts the quality of life (QOL) of individuals worldwide. However, the role of self-management and social support among CKD patients on their QOL remains understudied in India. Therefore, this study aims to find the correlation of self-management and social support on the QOL of CKD patients undergoing hemodialysis. Methods: This hospital-based cross-sectional study involved 110 adult CKD patients (mean (SD) age of 56 (±13.9) years, 73 % men) undergoing hemodialysis in two tertiary care hospitals in Ernakulam district. Face-to-face interviews with questionnaires, including World Health Organisation Quality of Life- Brief Version (WHOQOL-BREF), Medical Outcome Survey - Social Support Survey (MOS-SSS), and Hemodialysis Self-Management Instrument-18 (HDSMI-18) were used. Pearson correlation and simple linear regression analysis were done to find the correlation between self-management and social support with QOL. Findings: The mean (SD) QOL score was 56.27 (11.62), with the environment domain rating highest [62.47 (14.02)] and social relations lowest [52.12 (18.52)]. Mean (SD) self-management score was 41.12 (5.66) and mean (SD) social support score was 65.28 (18.21). Self-management (r = 0.382, p = 0.001) and social support (r = 0.309, p = 0.001) showed a moderate positive correlation with QOL. Discussion: Self-management and social support were moderately correlated with QOL. Strengthening self-management programs and social support networks are likely to improve the QOL of CKD patients undergoing hemodialysis.